WARISAN MULAVARMMAN: MAKNA DAN KEBIJAKAN STRATEGIS - Kusmartono, Vida Pervaya Rusianti (Balai Arkeologi Kalimantan Selatan, 2008)
Every individual who has attended a 12-years-elementary education must be familiar with the lndic influenced name of